A causal model of eating behaviors among Thai pregnant women working in industrial factories - Tachasuksri Tatirat; Ngamchay Chanapa; Nadarajan Sivasankari (Sciendo, 2024)
This study aimed to examine the causal model of eating behaviors among pregnant women working in industrial factories.